AN EVALUATION OF THE BASIC SEWING TRAINING CURRICULUM AT B4LAO TRAINING CENTER, SAVANNAKHET PROVINCE, LAO PEOPLE’S DEMOCRATIC REPUBLIC, USING THE CIPP MODEL - Suriyakham, Sirinuch; Jarutkamolpong, Suwisa; Thongpanit, Pichittra (Journal of Graduate School Sakon Nakhon Rajabhat University, 2025)
The purposes of this research were to evaluate the Basic Sewing Vocational Curriculum at the B4Lao Training Center in Savannakhet Province through the CIPP Model, comprising context, input, process and product. The research sample consisted of 42 participants, including two administrators, one sewing instructor, one foundation committee member, five current students, and 33 alumni. The data collection tools included structured interviews and a set of questionnaires. Data were analyzed using mean, standard deviation, and content analysis. The research results revealed that: 1) Context: The developed curriculum promoted practical skill development aligned with labor market and community needs and was rated overall at a high level of appropriateness, with a mean score of 4.33; 2) Input: Instructors demonstrated expertise, while students showed commitment to skill enhancement and effective resource management, which was rated overall at a high level of appropriateness, with a mean score of 3.95; 3) Process: The developed curriculum supported learning management in all aspects characterized by flexibility and alignment with students’ needs and was rated overall at a high level of appropriateness, with a mean score of 4.31; and 4) Product: Students and alumni showed significant improvement in sewing skills and personal development, enabling them to pursue their careers effectively, with an overall appropriateness rated at a high level, with a mean score of 3.83.